ATP release and Ca(2+) signalling by human bronchial epithelial cells following Alternaria aeroallergen exposure - O'Grady, Scott M (Blackwell Science Inc, 2013)
Exposure of human bronchial epithelial (HBE) cells from normal and asthmatic subjects to extracts from Alternaria alternata evoked a rapid and sustained release of ATP with greater efficacy observed in epithelial cells from asthmatic patients. Previously, Alternaria allergens were shown to produce a sustained increase in intracellular Ca(2+) concentration ([Ca(2+)](i)) that was dependent on the coordinated activation of specific purinergic receptor (P2Y(2) and P2X(7)) subtypes. In the present study, pretreatment with a cell-permeable Ca(2+)-chelating compound (BAPTA-AM) significantly inhibited ATP release, indicating dependency on [Ca(2+)](i). Alternaria-evoked ATP release exhibited a greater peak response and a slightly lower EC(50) value in cells obtained from asthmatic donors compared to normal control cells. Furthermore, the maximum increase in [Ca(2+)](i) resulting from Alternaria treatment was greater in cells from asthmatic patients compared to normal subjects. The vesicle transport inhibitor brefeldin A and BAPTA-AM significantly blocked Alternaria-stimulated incorporation of fluorescent lipid (FM1-43)-labelled vesicles into the plasma membrane and ATP release. In addition, inhibiting uptake of ATP into exocytotic vesicles with bafilomycin also reduced ATP release comparable to the effects of brefeldin A and BAPTA-AM. These results indicate that an important mechanism for Alternaria-induced ATP release is Ca(2+) dependent and involves exocytosis of ATP. Serine and cysteine protease inhibitors also reduced Alternaria-induced ATP release; however, the sustained increase in [Ca(2+)](i) typically observed following Alternaria exposure appeared to be independent of protease-activated receptor (PAR2) stimulation.